hnRNPA2B1 Associated with Recruitment of RNA into Exosomes Plays a Key Role in Herpes Simplex Virus 1 Release from Infected Cells - Zhou, Xusha (J Virol, 2020)
hnRNPA2B1, an abundant cellular protein, has been reported to recruit RNAs bearing a specific sequence (EXO motif) into exosomes. We characterized an exosome population averaging 100 ± 50 nm in diameter and containing a defined set of constitutive exosome markers. This population packages microRNAs (miRNAs) and can be directed to block targeted gene expression in a dose-dependent fashion. The objective of this study was to characterize the role of hnRNPA2B1 in the recruitment of miRNA. We report the following four key findings. (i) hnRNPA2B1 is not a component of exosomes produced in HEp-2 or HEK293T cells. Hence, hnRNPA2B1 carries its cargo, at most, to the site of exosome assembly, but it is not itself incorporated into exosomes. (ii) The accumulation of exosomes produced by cells in which the gene encoding hnRNPA2B1 has been knocked out (ΔhnRNPA2B1 cells) was reduced 3-fold. (iii) In uninfected HEp-2 cells, hnRNPA2B1 is localized in the nucleus. In cells infected with herpes simplex virus 1 (HSV-1), hnRNPA2B1 was quantitatively exported to the cytoplasm and at least a fraction of hnRNPA2B1 colocalized with a Golgi marker. (iv) Lastly, in ΔhnRNPA2B1 cells, there was a 2- to 3-fold reduction in virus yield but a significant (>10-fold) reduction in HSV-1 released through the apical surface into the extracellular environment. The absence of hnRNPA2B1 had no significant impact on the basolateral export of HSV-1 from infected to uninfected cells by direct cell-to-cell contact. The results suggest that hnRNPA2B1 plays a key role in the transport of enveloped virus from its site of assembly to the extracellular environment. IMPORTANCE In this report, we show that hnRNPA2B1 is not a component of exosomes produced in HEp-2 or HEK293T cells. In herpes simplex virus 1 (HSV-1)-infected cells, hnRNPA2B1 was quantitatively translocated from the nucleus into the cytoplasm. In infected ΔhnRNPA2B1 cells, Golgi-dependent transport of virus from the apical surface to the extracellular medium was significantly reduced. In essence, this report supports the hypothesis that hnRNPA2B1 plays a key role in the egress of exosomes and HSV-1 from infected cells.